Development of targeted multimodal imaging agent in ionizing radiation-free approach for visualizing hepatocellular carcinoma cells - Chalermchai Pilapong (2018)
© 2017 Elsevier B.V. Herein, we have developed a targeted imaging nanoprobe for visualizing EpCAM-positive cell lines, especially the hepatocellular carcinoma cell line (HepG2). Mesoporous silica-coated magnetic nanoparticles (mSiO2-MNPs) were first synthesized and then conjugated with EpCAM-specific aptamer (EpCAM aptamer) and fluorophore using appropriate bioconjugation routes. The EpCAM nanoprobe is utilized for multimodal imaging including MRI, US, and fluorescence with good physicochemical properties. The nanoprobe showed no toxicity toward either cancer cells (HepG2) or normal cells (PBMC), and demonstrated high cellular uptake in EpCAM+cancer cells, including HepG2, by endocytosis pathway. Apparently, polyvalent EpCAM nanoprobe-EpCAM receptor interaction is required to facilitate internalization across the cellular membrane. Because of high cellular uptake and imaging capability of the nanoprobe, it can be used to efficiently visualize the HepG2 cell using such imaging modalities. The study on the 3D spheroid model clearly confirms that EpCAM nanoprobe has the capability to penetrate into the tumor spheroid while EpCAM aptamer lacks the ability to penetrate into the spheroid on its own. Therefore, EpCAM nanoprobe can be used for targeted EpCAM+cancer cell imaging with the potential for improved tumor penetration. This development might lead to be a new biosensing technology, especially for imaging based in vivo detection.